The Edinburgh companion to James Hogg - Duncan, Ian (Edinburgh Univ. Press, 2012)
James Hogg (1770-1835) is increasingly recognised as a major Scottish author and one of the most original figures in European Romanticism. 16 essays written by international experts on Hogg draw on recent breakthroughs in research to illuminate the contexts and debates that helped to shape his writings. The book provides an indispensable guide to Hogg's life and worlds, his publishing history, reception and reputation, his treatments of politics, religion, nationality, social class, sexuality and gender, and the diverse literary forms - ballads, songs, poems, drama, short stories, novels, periodicals - in which he wrote.Key Features:Thorough coverage of the whole of Hogg's works, career and contexts, as well as detailed considerations of his most famous work, Private Memoirs and Confessions of a Justified SinnerThe contributors are all major figures in Hogg studies and include editors of the definitive Stirling South Carolina Research Edition of the Collected Works of James Hogg, including Caroline McCracken-Flesher (Wyoming), Hans de Groot (Toronto), Penny Fielding(Edinburgh), Peter Garside (Edinburgh) and Gillian Hughes
Keywords: Hogg, James -- 1770-1835; Literary Studies; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; English literature